What Is Nuclear Factor Kappa B (NF-κB) Doing in and to the Mitochondrion? - Albensi, Benedict C. (Frontiers in Cell and Developmental Biology, 2019)
A large body of literature supports the idea that nuclear factor kappa B (NF-κB) signaling contributes to not only immunity, but also inflammation, cancer, and nervous system function. However, studies on NF-κB activity in mitochondrial function are much more limited and scattered throughout the literature. For example, in 2001 it was first published that NF-κB subunits were found in the mitochondria, including not only IkBα and NF-κB p65 subunits, but also NF-κB pathway proteins such as IKKα, IKKβ, and IKKγ, but not much follow-up work has been done to date. Upon further thought the lack of studies on NF-κB activity in mitochondrial function is surprising given the importance and the evolutionary history of both NF-κB and the mitochondrion. Both are ancient in their appearance in our biological record where both contribute substantially to cell survival, cell death, and the regulation of function and/or disease. Studies also show NF-κB can influence mitochondrial function from outside the mitochondria. Therefore, it is essential to understand the complexity of these roles both inside and out of this organelle. In this review, an attempt is made to understand how NF-κB activity contributes to overall mitochondrial function – both inside and out. The discussion at times is speculative and perhaps even provocative to some, since NF-κB does not yet have defined mitochondrial targeting sequences for some nuclear-encoded mitochondrial genes and mechanisms of mitochondrial import for NF-κB are not yet entirely understood. Also, the data associated with the mitochondrial localization of proteins must be yet further proved with additional experiments.